2017
DOI: 10.1002/fut.21850
|View full text |Cite
|
Sign up to set email alerts
|

The impact of crude oil inventory announcements on prices: Evidence from derivatives markets

Abstract: This study examines the impact of weekly crude oil storage announcements on oil futures and options prices. We document evidence of a strong announcement day effect on both markets, and find prices to move in anticipation of the inventory surprise. Futures returns significantly decrease with positive surprises and increase with negative surprises. There is no evidence of an asymmetric impact on futures prices. Near‐the‐money options exhibit the greatest price sensitivity, and the magnitude of the price respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…That is, China's crude oil futures are traded more actively during the INE overnight session (e.g., through intermarket spreading) to incorporate the information relevant to the global oil market, when WTI futures are traded during its daytime trading session with regular and ample information release. Specifically, Miao, Ramchander, Wang, and Yang (2018) document that a set of rich information release, including the monthly U.S. macroeconomic announcements and weekly oil and related energy product inventory announcement exert significant impacts on the WTI oil futures and option markets, which obviously may well be transmitted to China's oil futures market.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, China's crude oil futures are traded more actively during the INE overnight session (e.g., through intermarket spreading) to incorporate the information relevant to the global oil market, when WTI futures are traded during its daytime trading session with regular and ample information release. Specifically, Miao, Ramchander, Wang, and Yang (2018) document that a set of rich information release, including the monthly U.S. macroeconomic announcements and weekly oil and related energy product inventory announcement exert significant impacts on the WTI oil futures and option markets, which obviously may well be transmitted to China's oil futures market.…”
Section: Resultsmentioning
confidence: 99%
“…On average, three pairs of correlations are higher than 70%, except for the pairs of the INE and the other two crude oil futures during the daytime trading. Thus, China's crude oil futures are rather well integrated with the global crude oil futures markets, especially during its overnight trading session when much information from the daytime session of the WTI and Brent markets is available (e.g., Miao et al, 2018). We also compare the average of each conditional correlation series to its unconditional counterpart and find that they are generally close to each other, validating the adequacy of empirical models used here.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are almost no studies of the eects of announcements on the term structure of futures prices. 6 One exception is Miao et al (2018). Six continuous contracts are analyzed in this paper, and the results indicate slow weakening of the magnitude of the price response with maturity, a 1% increase in inventories decreases the price of the rst month contract by 0.552%, the price of the second contract by 0.541%, and for the sixth contract by 0.343%.…”
Section: Introductionmentioning
confidence: 85%
“…Most studies dene a market surprise as the dierence between the reported EIA estimate and the median survey forecast. Given general public interest in oil inventories, various surveys are available that directly ask about agents' expectations of EIA announced changes, including the surveys conducted by Reuters and utilized in Bu (2014), Bloomberg, used by Halova Wolfe and Rosenman (2014), ), Miao et al (2018, and Platt's. By assumption, the weight placed on an API signal equals zero.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation